2009
DOI: 10.1001/archgenpsychiatry.2008.543
|View full text |Cite
|
Sign up to set email alerts
|

Tests of Causal Links Between Alcohol Abuse or Dependence and Major Depression

Abstract: The findings suggest that the associations between AAD and MD were best explained by a causal model in which problems with alcohol led to increased risk of MD as opposed to a self-medication model in which MD led to increased risk of AAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
326
3
15

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(369 citation statements)
references
References 38 publications
25
326
3
15
Order By: Relevance
“…Two reviews on this topic came to the same conclusion: that all three mechanisms are possible and probably existing, but the first mechanism—that alcohol use (especially heavy use and alcohol use disorders) causes depression—is stronger and more prevalent than the other pathways (5, 219; see also 221, 222). …”
Section: Resultsmentioning
confidence: 99%
“…Two reviews on this topic came to the same conclusion: that all three mechanisms are possible and probably existing, but the first mechanism—that alcohol use (especially heavy use and alcohol use disorders) causes depression—is stronger and more prevalent than the other pathways (5, 219; see also 221, 222). …”
Section: Resultsmentioning
confidence: 99%
“…An additional body of literature has assessed the temporal onset of MD and SUD without directly assessing SM, and found evidence for both causal pathways (Crum et al., 2013; Feingold et al., 2015; Fergusson et al., 2009; Kessler et al., 1997; Kuo et al., 2006; Lazareck et al., 2012; Liang et al., 2011; Martins et al., 2012; Wolitzky‐Taylor et al., 2012). Data from Australia showed that those with MD were at a higher risk of incident harmful or dependent drug use (Liang et al., 2011).…”
Section: Resultsmentioning
confidence: 99%
“…A study including three different geographic communities from the USA and Puerto Rico showed that the age of onset for alcohol abuse/dependence disorders and depressive disorders was evenly distributed, with about 50% of depressive disorders occurring before and 50% occurring after the onset of alcohol abuse/dependence (Swendsen et al., 1998). Using data from young adults of age 17–25 years in New Zealand, one study concluded that the strongest pathway existed for baseline alcohol abuse and dependence followed by incident major depression (Fergusson et al., 2009). Finally, using data from a large population‐based registry in Virginia, Kuo et al., 2006, found significant evidence for the pathway of baseline major depression, followed by the onset of alcohol dependence, and no significant evidence for the reverse pathway (Kuo et al., 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…V. Grant, Stewart, & Mohr, 2009;Kuo, Gardner, Kendler, & Prescott, 2006). Such reverse causality has been once previously examined through a structural equation model using New Zealand data (Fergusson, Boden, & Horwood, 2009), where alcohol abuse increased the risk of depression. However, the small sample size and the lack of exclusion restrictions implied strong assumptions for identification suggesting caution in drawing inferences.…”
Section: Introductionmentioning
confidence: 99%